Competitiveness of the Top Five Main Export Destinations of Indonesia's Crude Palm Oil (CPO) For 2011–2020 - Nur Asita Ariga YS; Tanti Novianti (Budapest International Research and Critics University, 2022)
Indonesia as the largest palm oil producing country in the world has the opportunity to compete in international trade. This study aims to analyze Indonesian CPO's comparative and competitive competitiveness in international trade. The analytical methods used are Revealed Competitive Advantage (RCA), Export Product Dynamics (EPD) and Trade Specialization Index (ISP). The data used are secondary data in the form of a time series for the period 2011 to 2020 and cross section of the main export destination countries for Indonesian palm oil, namely India, Spain, Malaysia, Italy and Kenya. The results of the analysis show that the RCA value of Indonesian palm oil exports in the five destination countries is greater than one, this indicates that Indonesian palm oil has a comparative advantage in the main export destination countries. When compared with the main CPO producer, RCA Indonesia is bigger than RCA Malaysia. Through ISP calculations, the main CPO producing countries, Indonesia and Malaysia, are countries that tend to become CPO exporting countries. Through the EPD analysis, the results show that the competitive position of Indonesian palm oil in the five export destination countries for the period 2011 to 2020 changes every year, this shows that Indonesian palm oil products do not always have a competitive advantage in the main export destination countries. Italy and Kenya are exporting countries with great potential for Indonesian CPO commodities, which each year are in the Rising Star position.